EVALUATION OF PIBID IN SUBPROJECT BIOLOGICAL SCIENCES FROM UNESP ASSIS - Simao, Felipe Pinto [UNESP]; Leite Barbosa, Raquel Lazzari (Univ Fed Rio De Janeiro, Fac Letras, 2017)
The research aimed to verify how the PIBID - Institutional Program of Initiation to Teaching Scholarship -, in the Biological Sciences subproject of UNESP Assis, contributed to the training of beginning teachers and the development of the students of participating public schools. Data collection included a bibliographical survey, questionnaires and interviews. The data allow us to conclude that the PIBID has contributed to the formation of new teachers by encouraging practical actions that take place during the internships in schools, as well as bringing scholarship recipients closer to everyday school life, critical-reflexive thinking, formative practices and Educational field.
Keywords: Teacher Training; PIBID; Initial formation